Multiplexed antigen microarray development for comprehensive immune health profiling: a proof of concept study - Thompson, Chloe (2024)
This proof-of-concept study introduces a versatile multi-antigen microarray platform for comprehensive serological profiling of adaptive humoral immune responses. Such a platform is required as autoantibodies can be detected in sera years before symptom manifestation and the clinical onset of autoimmune disease. However, traditional ELISAs used to assess one antibody biomarker at a time are relatively time-consuming, costly and reductive. Alternatively, to detect broad-scale antibody reactivities, we developed a custom microarray that can simultaneously quantify IgG and IgA responses against 60 antigens, including autoantigens, pathogen-associated, and viral recall antigens, using sub-microlitre volumes of patient sera. Our platform was applied to 128 individuals: 11 diagnosed with cystic fibrosis, 63 with C. difficile infection (CDI), 24 with recurrent CDI (pre- and post-faecal microbiota transplantation; FMT), and 30 healthy controls. Antigens were printed on nitrocellulose slides, probed with sera and scanned for antibody-antigen interactions. Across sixty antigens, 93% of intra-assay variabilities and 90% of inter-assay variabilities fell below the precision limit of <20% coefficient of variation (CV). Distinct heterogeneity was observed in adaptive humoral responses across samples, enabling patient clustering based on antigen-specific IgG and IgA responses. Profiles displayed rare yet strong autoantibody responses across samples, indicating the presence of preclinical or natural autoantibody repertoires. Recurrent CDI sera was tested pre- and post-FMT, and found that FMT did not significantly alter humoral responses after 12 weeks, indicating the need for long-term analysis in larger cohorts. Lastly, differences in antigen-specific IgG and IgA humoral responses distinguished initial and recurrent CDI patients, providing insights into CDI adaptive immunity. In summary, our preliminary assay highlights the potential for efficient and scalable immune health screening. With further research, implementing multiplexed antigen microarrays in healthcare systems could enable annual immune health screening as an early warning system for immune-mediated diseases and multimorbidity, with potential advantages in throughput and cost-efficiency.